God, Politics, and Initial Teacher Education (ITE): An Exploration of Pre-service Teachers' Socio-politico-religious Identifications - Adam, Raoul (Journal for the academic study of religion, 2025)
Teacher education has an essential role in facilitating dialogue between diverse socio-politico-religious perspectives. This study used a mixed methods survey (N = 1179) to examine intragroup differences among pre-service teachers (PSTs) across the Left-Right Spectrum (LRS), the Theist-Atheist Spectrum (TAS), and identifications with Ultimate Concepts. Findings showed that PSTs tended to identify as centre left and theistic-agnostic; that gender significantly predicted TAS identification, with female PSTs more likely to be theistic; that TAS and LRS were significantly related, with theism associated with more right-leaning positions; and that PST demographics were significantly interrelated. We interpret these findings to support (a) inclusive approaches in Initial Teacher Education that represent and reconcile socio-politico-religious differences, and (b) further research on disciplinary affiliation and identity. We situate these insights within contemporary debates about the teaching profession's role amid growing disruption and polarisation in Western democracies.